1998
DOI: 10.1136/bmj.317.7166.1125
|View full text |Cite
|
Sign up to set email alerts
|

Implications of applying widely accepted cholesterol screening and management guidelines to a British adult population: cross sectional study of cardiovascular disease and risk factors

Abstract: Objective: To compare the implications of four widely used cholesterol screening and treatment guidelines by applying them to a population in the United Kingdom. Design: Guidelines were applied to population based data from a cross sectional study of cardiovascular disease and risk factors. Setting: Newcastle upon Tyne, United Kingdom. Subjects: General population sample (predominantly of European origin) of 322 men and 319 women aged 25-64 years. Main outcome measures: Proportions recommended for screening an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 21 publications
0
19
0
1
Order By: Relevance
“…Like previous recommendations the new guidelines fail to adequately address the service consequences of their policies18 and leave primary care with an unresolved dilemma. Should lipid concentrations be measured in all adults, using the joint British tables, in 70% of the population, using the Sheffield tables, or in 15% of the population, using average lipid values rather than actual measured values?…”
Section: Screening Lipid Measurement and The Lower Limitmentioning
confidence: 91%
“…Like previous recommendations the new guidelines fail to adequately address the service consequences of their policies18 and leave primary care with an unresolved dilemma. Should lipid concentrations be measured in all adults, using the joint British tables, in 70% of the population, using the Sheffield tables, or in 15% of the population, using average lipid values rather than actual measured values?…”
Section: Screening Lipid Measurement and The Lower Limitmentioning
confidence: 91%
“…However, a previous study showed that, although national guidelines varied, the NCEP guidelines would treat more patients than several other international guidelines. 29 Thus, this would not explain the association between international medical graduates and increasing overprescribing. In addition, the definition of oral agent was left to the respondent.…”
Section: Discussionmentioning
confidence: 97%
“…They may be aware that results may be conflicting from one source to another [26,27] and may wonder whether their physician's decision is based on formal or informal consensus, or on evidence-based or explicit guidelines, all of which can yield different results. Some authors have shown that practice guidelines are seldom followed in everyday medical practice [28], suggesting that physicians are reluctant to use them.…”
Section: Practice Guidelines: Their Variety and Qualitymentioning
confidence: 97%